Szczególna ochrona socjalistycznej własności państwowej a własność osobista w świetle wybranych rozwiązań cywilnoprawnych w PRL - Kozińska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This study is a short analysis of the impact of ideological assumptions in the People’s Republic of Poland on the civil law issue of property. The aim formulated at the outset of the study was to demonstrate that the assumptions of the Marxist-Leninist doctrine and the ideology of building a socialist system were decisive for the introduction of civil law norms, which were to serve strengthening and development of socialist state property. Nevertheless, judicial activity also performed a support function. The second point generally explains the problems of the functions that were assigned to socialist nationwide (state) property and personal property in the People’s Republic of Poland. Next, the author selected and examined legal solutions that constituted examples of legislation aimed at implementing the principle of special protection of socialist state property. The scope of the research covered the relevant provisions of the Civil Code 1964, which were to ensure the primacy of state property or privilege state organizational units exercising state property rights. Exemplary the Supreme Court judicature concerning the analysed civil law provisions was also examined. Against this background, a clear inequality in the protection of state and personal property has emerged. In the conclusion of the study, it was stated that the legislative activity in the People’s Republic of Poland in the field of civil law implemented the ideological assumptions imposed by the Constitution 1952 concerning the protection of socialist state property. Ideological postulates also had a certain impact on the judicature, which supported the People’s Republic of Poland as a people’s state through interpretation, as well as by filling in the legal loopholes in the laws securing and strengthening state property.
Keywords: ustrój socjalistyczny; marksizm-leninizm; socjalistyczna własność państwowa; własność osobista w PRL; własność ogólnonarodowa w PRL